2019
DOI: 10.11648/j.ajls.20190705.12
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Zinc Deficiency Among Pregnant Women Attending Antenatal Care at Gambella Hospital, Gambella, Ethiopia, 2018

Abstract: It has been evidenced that zinc deficiency has an adverse effect on both mother and fetus, and subsequent birth outcomes and child survival. However, data on the prevalence and determinants of zinc deficiency among pregnant women are scanty in the country. Thus, this study was aimed to assess the prevalence of zinc deficiency and its associated factors among pregnant mothers attending antenatal care in the study setting in particular and the country in general. Hospital based crosssectional study was done in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Furthermore, the study conducted in Padang Indonesia also found low serum zinc levels during pregnancy (36.01 ± 18.34 µg/dL) [32]. Similarly, a study from Ethiopia reported an average serum zinc level in pregnant women of 58.75µg/dL, with a prevalence of zinc deficiency of 55.3% [33]. In the Egyptian study, the zinc deficiency occurred was 53.5% [34].…”
Section: Serum Zinc Levels For Pregnant Womenmentioning
confidence: 87%
“…Furthermore, the study conducted in Padang Indonesia also found low serum zinc levels during pregnancy (36.01 ± 18.34 µg/dL) [32]. Similarly, a study from Ethiopia reported an average serum zinc level in pregnant women of 58.75µg/dL, with a prevalence of zinc deficiency of 55.3% [33]. In the Egyptian study, the zinc deficiency occurred was 53.5% [34].…”
Section: Serum Zinc Levels For Pregnant Womenmentioning
confidence: 87%
“…Preferred reporting items for systematic reviews and meta-analysis (PRISMA) checklist was used during the review [14]. Published articles, survey reports, and grey literature (one paper) [15] which were published or reported in English were considered in this meta-analysis. Due to the limited number of studies conducted in Ethiopia, and to increase the comprehensiveness of the meta-analysis, all eligible studies published or reported till May 30, 2019, were included in this systematic review and meta-analysis.…”
Section: Eligibility Criteria and Information Sourcesmentioning
confidence: 99%
“…After assessing the full texts of the 19 records for their eligibility, 6 records [21][22][23][24][25][26] were further excluded by the exclusion criteria. Finally, 13 studies, 7 for pregnant women [15,[27][28][29][30][31][32] and 6 for children [11,[33][34][35][36][37], were found to be eligible for this systematic review and meta-analysis ( Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Projected worldwide, above 82% of women during gestation have insufficient intake of zinc (Caulfield et al 1998). Globally, in Ethiopia the prevalence of zinc deficiency among pregnant women was 55.3% (Mekonnen et al 2018), in India 64-72% (Pathak et al 2008), in Sidama 53% (Gebremedhin et al 2011), in Gondar 57.4% (Kumera et al 2015), in China 51.5% (Ma et al 2004), in Nigeria 97.2% (Oguizu AD 2015), in Kenya 66.9% (Mitheko 2013), in Turkey 72.3% (Açkurt 1995) in Pakistan 27.8% (Lutfullah 2014), in Sudan 45% (Shommo et al 2013), in Malawi 46% (Gibson and Huddle 1998), in Iran 29% and 49% (Roshanravan et al 2015), in Vietnam 29% (Nguyen et al 2013) and in Bangladesh 14.7% (Shamin et al 2013). Several researches involved different population by culture and geographical area which may contribute to the differences in the incidence of zinc deficiency during pregnancy (Severi et al 2013).…”
Section: Prevalence Of Zinc Deficiency In Pregnancymentioning
confidence: 99%